Sex, Gender and Substance Use - Greaves, Lorraine (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
"Sex, Gender and Substance Use" describes how both biological and social factors affect people's use of substances. There is a lot of research carried out on substance use, prevention and treatment in which sex and gender are missing. This book describes the concepts of sex and gender, what they mean and why including them in substance use research, practice and policy is vital. Substances such as alcohol, drugs, nicotine, and tobacco all have differential effects on females and males. Social and cultural gendered factors affect how women and men react to prevention, treatment and policies. The book includes numerous examples of how sex- and gender-sensitive research can increase our understanding and improve prevention and treatment, and why striving for gender-transformative substance use practice and research remains a gold standard.